The general equation of a circle is expressed as
![\begin{gathered} (x-a)^2+(y-b)^2=r^2\text{ ----- equation 1} \\ \text{where} \\ (a,\text{ b)}\Rightarrow\text{ center of the circle} \\ r\Rightarrow radius\text{ of the circle} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/a8rm6blbo6u4sru5sdjoa9yovqf0tv3ucv.png)
Given that a circle having equation
![\begin{gathered} (x-2)^2+(y-5)^2\text{ = 16} \\ \Rightarrow(x-2)^2+(y-5)^2\text{ = }4^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mfxl73oesq4ric6kc74uc58o9m5e1bxqxe.png)
is moved up 3 units and 1 unit to the left. Thus, we have
![\begin{gathered} (x-2+1)^2+(y-5-3)^2\text{ = }4^2 \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/st7d32ivwarj2zf83umrnqcu5d4do8bo0q.png)
This gives
![(x-1)^2+(y-8)^2\text{ = }4^2\text{ ----- equation 2}](https://img.qammunity.org/2023/formulas/mathematics/college/izasbkax795i5i7ghygwed1jnxv7790fe0.png)
Comparing equations 1 and 2, we have
![a\text{ = 1, b = 8, r = 4}](https://img.qammunity.org/2023/formulas/mathematics/college/zdo87za7ujauu55k84443arzk2f189a64g.png)
Hence,
the center (a, b) of the circle is (1, 8),
the radius r of the circle is 4,
the equation of the circle is
![(x-1)^2+(y-8)^2=4^2](https://img.qammunity.org/2023/formulas/mathematics/college/1mkjc7bzdswix8kb7afwgqephswq4dmtz1.png)